Micro-textures and in situ sulfur isotopic analysis of spheroidal and zonal sulfides in the giant Jinding Zn–Pb deposit, Yunnan, China: Implications for biogenic processes. (1st May 2015) - Xue, Chunji; Chi, Guoxiang; Fayek, Mostafa
Abstract : Graphical abstract: Highlights: Spheroidal and zoned sulfide textures from the Jinding Zn–Pn deposit interpreted to be biogenic. Depleted sulfur isotopic compositions analyzed by SIMS resulted from in situ BSR. The Jinding deposit formed from episodic hydrothermal events at low ambient temperature. Abstract: The Jinding deposit in Yunnan, southwest China, is the largest sandstone- and conglomerate-hosted Zn–Pb deposit in the world. In this paper, we report various micro-textures of spheroidal and zonal sulfides, such as pellet-shaped and colloform aggregates of pyrite and sphalerite, from the deposit and interpret them to be possibly related to micro-colonies of sulfate reducing bacteria, probably supporting an in situ BSR hypothesis. Micro-scale sulfur isotope analysis in different parts of the spheroidal and zonal sulfide aggregates, using secondary ion mass spectrometry (SIMS), revealed δ 34 S (VCDT) values as low as −48.4‰ for sulfides formed in the early-main stage disseminated ores in the western part of the deposit, possibly suggesting maximum sulfur isotopic fractionation through BSR. Relatively elevated δ 34 S (VCDT) values (−7.7‰ to −34.8‰, mainly from −10‰ to −20‰) for the late-stage, cavity-filling ores in the eastern part of the deposit, are interpreted to be possibly related to elevated temperatures close to the hydrothermal conduit and elevated δ 34 S values of the remaining sulfates resulting from the preceding BSR processes. The apparent discrepancy between the low temperatures required for BSR and the high temperatures indicated by fluid inclusions (>120 °C) may be reconciled through invoking episodic influx of ore-forming hydrothermal fluids into a shallow, relatively cool environment. It is proposed that the host rocks of the Jinding deposit have not been buried to great depths (⩽1 km), which, combined with the availability of hydrocarbons in the Jinding dome (a paleo-oil and gas reservoir), provides an ideal environment for BSR. Episodic influx of metal-carrying hydrothermal fluids temporarily and locally suppressed BSR and promoted thermo-chemical sulfate reduction (TSR), resulting in deposit- and micro-scale variations of δ 34 S.